Pengaruh Perbandingan Modified Cassava Flour (Mocaf) dan Puree Labu Kuning (Cucurbita Moschata) Terhadap Karakteristik Brownies Kukus - Anggi Putri Arina, I Gusti Agung; Timur Ina, Putu; Ekawati, I Gusti Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2021)
The study aims to determine the effect comparison of mocaf with pumpkin puree to the characteristics of steamed brownies and to find out the best comparison mocaf with  pumpkin puree to produce brownies with the best characteristics. The experimental design used in this research was a Completely Randomized Design (CRD) with a comparison of mocaf and puree of pumpkin consisting of 5 treatments namely: 100%: 0%; 90%: 10%; 80%: 20%; 70%: 30%; 60%: 40%. The treatment was repeated 3 times so that they were obtained 15 experimental units. The data obtained were analyzed by variance and if the treatment had significant effect then followed by Duncan’s Multiple Range Test (DMRT). Comparison of mocaf and pumpkin puree affected water content, ?-carotene, ?-carotene bleaching, hedonic test (color, texture, aroma, taste and overall rate) and scoring test (texture). Ratio of 60% mocaf and 40% puree of pumpkin had the best characteristics with water content of 34,49%, ash content of 1,10%, ?-carotene of 6,82 mg/100g, ?-carotene bleaching of 1,34 mg/ml, the texture was liked and very soft, the color, aroma, taste and the fullness of acceptance was liked.